Estimation of solar and wind energy resources over Lesotho and their complementarity by means of WRF yearly simulation at high resolution. (October 2020) - D'Isidoro, Massimo; Briganti, Gino; Vitali, Lina; Righini, Gaia; Adani, Mario; Guarnieri, Guido; Moretti, Lorenzo; Raliselo, Muso; Mahahabisa, Mabafokeng; Ciancarella, Luisella; Zanini, Gabriele; Fino, Ernesto
Abstract: An application of the Weather Research and Forecasting model aiming to estimate wind and photovoltaic energy resources over Lesotho is presented. To this scope, the whole year 2015 was simulated in a two-way nesting mode reaching 1 km horizontal resolution. Different model parameterizations were tested and compared to available observations, then the best performing simulation was used to elaborate wind and photovoltaic potential maps over Lesotho. Concerning the photovoltaic potential, Lesotho presents a good potential countrywide, having values ranging from around 1600 kWh/kWp to 1750 kWh/kWp, with maxima in the highlands. The results also show that there are many promising areas for wind power exploitation. Zones with higher wind potential are mainly found all along the eastern border with South Africa, from north to south and in general in the highlands. The wind potential exhibits much more variability respect to the photovoltaic one, with estimated energy production ranging from 1000 kWh/kW up to 4000 kWh/kW. Finally, an evaluation of complementarity of wind and solar electricity generation was done at different time scales, showing that some areas with negative correlation coefficient exist, where it is possible to minimise intermittent production and allowing an optimal integration in the electricity grid. Highlights: Assessment of photovoltaic and wind energy resource over Lesotho is presented. A numerical atmospheric model is tuned and used for the evaluation. For the first time 1 km resolution energy potential maps are produced over Lesotho. Complementarity of wind and photovoltaic electricity generation in time is explored.